Honesty in psychotherapy: Results of an online survey comparing high vs. low self-concealers. (3rd September 2019) - Love, Melanie; Farber, Barry A.
Abstract: Objectives: This study sought to investigate client dishonesty in psychotherapy through the trait of self-concealment. We hypothesized that comparing low and high self-concealers would yield clinically significant differences in the nature, motives, and perceived consequences of client dishonesty. Method: A total of 572 respondents, self-reported as psychotherapy clients, reported about their experience of being dishonest in therapy via a multi-part online survey. Concealment status was assessed using the Self-Concealment to Therapist Scale, an adaptation of the Self-Concealment Scale. Results: Eighty-four percent of respondents reported having been dishonest about one or more topics in therapy, most often "details of my sex life" and "suicidal thoughts." High self-concealers reported more relationally oriented motives for dishonesty and acknowledged more negative effects on therapy than low self-concealers. In contrast, low self-concealers were more likely to report that non-disclosure was based on motives of practicality (e.g., managing therapy time), and that they would be willing to disclose if the therapist asked directly. Conclusions: Low and high self-concealers showed distinct patterns of motives, perceived consequences, and attitudes about facilitating disclosure in therapy. This suggests that self-concealment may be an important variable in tailoring treatment to foster greater and more honest disclosure. Clinical or Methodological Significance of this article: This article adds to the burgeoning literature on dishonesty in psychotherapy and presents a novel exploration of how self-concealment can be used to individually tailor treatment to facilitate increased levels of honest disclosure. High levels of self-concealment, or the trait-like tendency to conceal negative or distressing personal information from others, have been associated with deleterious long-term health and interpersonal effects. By exploring clients' motives for being dishonest, as well as their perception of how it impacted therapy and their self-identified techniques for how therapists can foster more honest, we provide specific clinical recommendations to increase disclosure in psychotherapy.